SPATIAL DISTRIBUTION OF SOME CHEMICAL CHARACTERISTICS OF AN ACID SULFATE SOIL-AFFECTED BRACKISHWATER PONDS IN THE COASTAL AREA OF LUWU REGENCY SOUTH SULAWESI PROVINCE - Erna Ratnawati; Akhmad Mustafa (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Spatial distribution of brackishwater pond soil has important role in the system of bioenvironment including brackishwater pond environment. This research was aimed to determine the spatial distribution of some chemical characteristics of an acid sulfate soil-affected brackishwater pond in coastal area of Luwu Regency South Sulawesi Province, Indonesia. ALOS AVNIR-2 images (acquisition 16 May 2008, 16 October 2008, 17 September 2009) were integrated with Indonesian Topographic maps to obtain base map. Sampling soil points were determined by simple random sampling in 104 points for two different soil depths i.e. 0-0.2 m and 0.5-0.7 m. A total of 18 soil chemical characteristics was measured in the field and analyzed in the laboratory. Geostatistic using kriging method in the ArcGIS 9.3 software was used to interpolate the data. The results of this study indicated that in general pond soil chemical characteristics in Luwu Regency could be categorized with high variability or relatively heterogenic wi th the value of var iation coefficient more than 36%. The soil characteristics that explain acidity had shown similar pattern in spatial distribution as well as other soil characteristics with soil nutrient. The high value of pH and low value of PO4 were generally found in the northern part of Luwu Regency, including East Lamasi, East Walenrang, Bua, and Ponrang Subdistricts. It is recommended that soil management in brackishwater ponds of Luwu Regency could be based on soil chemical characteristics so its could improve the production through minimizing the input, increasing carrying capacity, and avoiding environmental degradation.